Impact design features firing furnaces at adequacy test results to fire bearing walls - Nuyanzin, Александр; Sidney, Станислав; Fedchenko, Игорь (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2016)
We show the basic principles of mathematical model of fire testing furnace load-bearing walls in full system Navier-Stokes equations using program complex CFD FlowVision 2.5. A computational experiment in the created model. Highlight features that may affect the adequacy of the results of fire tests bearing walls.